2018 IEEE/CVF Conference on Computer Vision and Pattern Recognition 2018
DOI: 10.1109/cvpr.2018.00481
|View full text |Cite
|
Sign up to set email alerts
|

ScanComplete: Large-Scale Scene Completion and Semantic Segmentation for 3D Scans

Abstract: 3D scans of indoor environments suffer from sensor occlusions, leaving 3D reconstructions with highly incomplete 3D geometry (left). We propose a novel data-driven approach based on fully-convolutional neural networks that transforms incomplete signed distance functions (SDFs) into complete meshes at unprecedented spatial extents (middle). In addition to scene completion, our approach infers semantic class labels even for previously missing geometry (right). Our approach outperforms existing approaches both in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
272
0
2

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 296 publications
(274 citation statements)
references
References 47 publications
0
272
0
2
Order By: Relevance
“…We report true positive (TP) rate of completion, average surface distance to the ground truth, semantic accuracy (SA) and free-space accuracy (FA). The comparison demonstrates that our method performs better than the baselines [6,14].…”
Section: Stereo Expert Systemmentioning
confidence: 94%
See 1 more Smart Citation
“…We report true positive (TP) rate of completion, average surface distance to the ground truth, semantic accuracy (SA) and free-space accuracy (FA). The comparison demonstrates that our method performs better than the baselines [6,14].…”
Section: Stereo Expert Systemmentioning
confidence: 94%
“…Top row: Estimated confidence values from input measurement on ScanNet dataset. Middle and bottom rows: The proposed learned fusion in comparison to datacost averaging in [6], ScanComplete [14] and ground truth.…”
Section: Kinect Confidencesmentioning
confidence: 99%
“…We conduct experiments on the SUNCG dataset [32] to verify the effectiveness of our method. For training and evaluation, we create virtual scans of the synthetic scenes, where we simulate a large-scale indoor 3D reconstruction by using rendered depth frames similar to [14,8] with the distinction that we add noise to the synthetic depth frames in the fusion process. The voxel resolution for the generated SDF grids is at 4.68cm.…”
Section: B Suncgmentioning
confidence: 99%
“…SSCNet [40] combined these two tasks together and showed that segmentation and completion can benefit from each other. In order to generate high resolution 3D structure, various methods had been explored, such as long short-term memorized [15], coarse-to-fine strategy [5], 3D generative adversarial network [47], and inverse discrete cosine transform [22]. Recently, segmentation and completion are both benefited from these advanced 3D deep learning methods described in section 2.1.…”
Section: Semantic Segmentation and Shape Completionmentioning
confidence: 99%